2018
DOI: 10.1029/2018wr022871
|View full text |Cite
|
Sign up to set email alerts
|

Approaches for Estimating Soil Water Retention Curves at Various Bulk Densities With the Extended Van Genuchten Model

Abstract: Soil bulk density (ρb) variations influence soil hydraulic properties, such as the water retention curve (WRC), but they are usually ignored in soil water simulation models. We extend the van Genuchten WRC model parameters to account for ρb variations using a series of empirical expressions. WRC measurements made on eight soils with various ρb, and textures are used to calibrate these ρb‐related empirical equations. Accordingly, two approaches are developed to estimate WRCs of soils at various ρb. Another eigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 56 publications
1
32
0
1
Order By: Relevance
“…However, results indicated large differences in θ v for different ρ b at −50 kPa. Even at −1500 kPa differences were still evident, contradicting the results of Ahuja et al (1998); as well as modeling assumptions that at low Ψ, the water retention for different ρ b is similar (Tian et al, 2018a). In-situ water retention measurements for a sandy soil (Zhang et al, 2017, Table 1) showed markedly similar changes in water retention, with water contents at −33 kPa ranging from 0.15-0.20 cm 3 cm −3 for a ρ b of˜1 g cm −3 and 0.28 cm 3 cm −3 for a ρ b of 1.33 g cm −3 .…”
Section: Discussionmentioning
confidence: 61%
See 4 more Smart Citations
“…However, results indicated large differences in θ v for different ρ b at −50 kPa. Even at −1500 kPa differences were still evident, contradicting the results of Ahuja et al (1998); as well as modeling assumptions that at low Ψ, the water retention for different ρ b is similar (Tian et al, 2018a). In-situ water retention measurements for a sandy soil (Zhang et al, 2017, Table 1) showed markedly similar changes in water retention, with water contents at −33 kPa ranging from 0.15-0.20 cm 3 cm −3 for a ρ b of˜1 g cm −3 and 0.28 cm 3 cm −3 for a ρ b of 1.33 g cm −3 .…”
Section: Discussionmentioning
confidence: 61%
“…Unfortunately no data at −1500 kPa were available for higher bulk densities. Using fitted θ r rather than θ v at −1500 kPa, an alternative suggested by Tian et al (2018a), did not improve Approach 1 as it resulted in θ r > θ v at −1500 kPa. This unreasonable result is likely due to the bimodal nature of the water retention curves (data not shown).…”
Section: Soil Water Retentionmentioning
confidence: 96%
See 3 more Smart Citations